The political dimensions of a writing: The case of Quechua in Peru - Jung, Ingrid (1987)
Since recent times the "problem" of writing in Quechua is once again on the table and this is due to the fact that indigenous education is also taking a different course given the progress, albeit slowly increasing, of educational experiences that make use of this language as a vehicle of education. At the moment, these experiences are only aimed at the vernacular-speaking rural population and, unfortunately, there are still no attempts at Quechua-Spanish education for the bilingual or monolingual Spanish-speaking urban population. This distinction seems important to us in the discussion that we will develop, since it is closely linked to the use of the Quechua alphabet.